Pengaruh Dukungan Keluarga dan Sosial Pada Peningkatan Status Kesehatan dan Self-Care Managemen Diabetes Melitus: Tinjauan Sistematis - Karingga, Devangga Darma; Indah Jayani; Idola Perdana Sulistyoning Suharto; Moh Alimansur; Eva Dwi Ramayanti (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
The prevalence of type 2 diabetes mellitus (T2DM) is increasing in low- and middle-income countries, caused by obesity, unhealthy eating patterns, sedentary behavior, and aging. Social support, both from family and friends, is recognized as an important factor in improving health habits and disease management, especially in the case of diabetes. Family education of patients with T2DM can improve self-care behavior and motivation, playing a key role in the concept of family-centered empowerment. This research used a systematic review, where articles were searched in four leading databases, namely Scopus, ProQuest, ScienceDirect, and SAGE, starting from early May 2024. The search was carried out using a combination of keywords and MESH terminology related to family and social support in diabetes mellitus patients. Articles selected for review were then evaluated in depth by researchers using JBI critical appraisal tools to address bias. Based on the selection of articles, a total of 10 articles were deemed appropriate for researchers and stated that they had significant results and statements regarding the influence of family and social support in the self-care management of diabetes mellitus sufferers. Family and social support have an impact on diabetes patients through both face-to-face interventions and telenursing, highlighting the ongoing need for continuous support.